(untitled) (Historia, 2021)
With the film Goodbye Lenin, audiences the world over were enchanted by the humoristic depiction of citizens of the former German Democratic Republic entering the post-Cold War world. With a more recent production, The lives of others, many filmgoers were left with an impression of East Germany as a starkly sinister place. With his book Zwischen Solidarität und Wirtschaftsinteressen, Ulrich van der Heyden offers South Africans a thoroughly alternative way to reflect upon the German Democratic Republic (hereafter GDR) past: by looking into the way the people and the government of their own country interacted with the GDR throughout its existence in the last half of the twentieth century, he illustrates the tug-of-war between principles and economic realities for two states which upheld highly conflicting ideologies, but, ironically, due to the weight of those very ideologies, shared a culture of centralised control, censorship and public surveillance. The title of the book translates as follows: "Between solidarity and economic interests: The 'secret' relations of the GDR with the South African apartheid regime".